Chemo-Entrepreneurship (CEP) Essentials: Practical Videos on Functional Group Material via YouTube - Nurul Umah; Agus Kamaludin (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
Entrepreneurship is crucial for students to navigate intense competition in the globalized era. Chemo-entrepreneurship (CEP) integrates chemistry education with the production of marketable products, which can serve as practical videos to illustrate the application and relevance of functional group materials in daily life, making chemistry learning more impactful when applied practically. This research aims to develop YouTube content in the form of practical videos on functional group material containing chemo-entrepreneurship. The method used in this research is research and development (R&D) with a define, design, develop, and disseminate (4-D) model. The products developed are assessed by material, media, and educational practitioner experts using product quality assessment sheets and student responses. The percentage of assessments from material, media experts, and reviewers are 87, 96, and 91%, respectively. Students responded positively to the practical video that was developed and obtained a percentage of 97%. Assessments from experts, reviewers, and students are in the very good category. Based on the data obtained, the practical video developed is suitable for use as an alternative media in practical learning of functional group material to improve students' entrepreneurial spirit.